A hipertrofia muscular esquelética proporcionada pelo exercício físico reflete no sinal eletromiográfico? uma revisão sistemática - Santos, Luis Eduardo Peixoto Rosa dos (2022)
Introduction: Skeletal striated muscle hypertrophy (PH) is referred to as an increase in the total mass of a muscle. The most accepted theory says that muscle hypertrophy is due to the trace of contractile proteins and an increase in the number of sarcomeres. This condition can be stimulated through different types of exercises and observed by electromyography (EMG). Objective: To verify, through a systematic literature review, whether the skeletal muscle hypertrophy provided by physical exercise is reflected on the EMG signal. Method: This systematic review were carried out according to the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), having as sources studies that used EMG to verify post-training muscle hypertrophy and that were published between January 1990 and November 2022 in English, Portuguese or Spanish. These studies were collected from Science Direct, Embase, MEDLINE, PEDro, SciELO, CINAHL, and LILACS databases. The terms “musculoskeletal hypertrophy”, “physical training” and “electromyography” were verified as Medical Subject Headings (MeSH) of the National Library of Medicine and their respective entry terms and later added to the search fields to make the search more sensitive and effective. The terms used for the search were: “skeletal muscle hypertrophy” AND “clinical trial”, “physical training” AND “clinical trial”, “electromyography” AND “hypertrophy”. Results: 8,021 studies were found using the keywords. However, only five studies were considered eligible, two studies had good methodological quality, but on the other hand, all of them had a considerably high risk of bias. Two studies had an increase in the cross-sectional area (CSA) and an increase in the EMG amplitude, one study an increased CSA but the EMG signal did not change, one study showed an increase in CSA and a decrease in the EMG signal and one study showed no change for CSA and no change in EMG signal. Conclusion: In this systematic review, it was not possible to find evidence that musculoskeletal hypertrophy, resulting from physical training, can be reflected by EMG electromyographic activity. We believe that the different study protocols, normalization, collection, and processing of the EMG signals, had a great influence on the result. Finally, we reinforce the idea of a better standardization of protocols and the need for further studies on this topic.